PERFORMANCE OF YANKASA RAMS FED CORN COB BASAL DIET SUPPLEMENTED WITH MIXTURE OF SUN-DRIED BROILER LITTER AND DIFFERENT ENERGY SUPPLEMENTS - Zagi, S. P.; Mahmud, M. (FUDMA JOURNAL OF SCIENCES, 2022)
A total of sixteen (16) Yankasa rams of about 10-12 months of age and having an average weight of 24 kg were used in an 84-day trial to investigate the nutrient utilization and digestibility of Yankasa rams fed grounded corn cob as basal diet supplemented with sun-dried broiler litter (SDPL) and different energy concentrate mixture. The rams were randomly assigned into four (4) treatments with four (4) replicates per treatment in a completely randomized design (CRD).  Four experimental diets were formulated and designated as: T1 (Corn cob + 150g SDPL + 150g MB), T2 (Corn cob + 150g SDPL + 150g RB), T3 (Corn cob + 150g SDPL + 150g MO), and T4 (Corn cob + 150g SDPL + 150g WO) and used to feed the Yankasa rams. The result of the performance of the rams showed that basal feed intake (35360.00-37735.00g; P
Keywords: Corn Cob, Rams, Diets, Sun-Dried Poultry Litter and Supplements